Dietary and plasma blood α-linolenic acid as modulators of fat oxidation and predictors of aerobic performance - Aleksandra Y. Lyudinina; Ekaterina A. Bushmanova; Nina G. Varlamova; Evgeny R. Bojko (Taylor & Francis Group, 2020)
Background Among n-3 polyunsaturated fatty acids (PUFAs), the most important is α-linolenic acid (ALA). The biological activity of ALA is not equivalent to that of the long-chain n-3 PUFAs, and it has pleiotropic effects, such as functioning as an energy substrate during long-term training when carbohydrate reserves are depleted. The purpose of this investigation was to study the link between the essential dietary and plasma ALA and aerobic performance, which is estimated via maximal fat oxidation (MFO), among skiers. Methods Twenty-four highly trained male athletes from the Russian cross-country skiing team participated in the study. ALA intake was determined by an original program used to assess the actual amount and frequency of fat consumption. The plasma level of ALA was determined using gas-liquid chromatography. The skiers' aerobic performance was estimated via MFO and determined by indirect calorimetry using the system "Oxycon Pro". Results The consumption of ALA in the diet in half of the skiers was below the recommended level at 0.5 ± 0.2 g/day. The deficiency of plasma ALA levels was on average 0.2 ± 0.1 Mol% for almost all participants. The consumption of ALA in the diet and its level in plasma were associated with MFO (rs = 0.507, p = 0.011; rs = 0.460, p = 0.023). Levels of ALA in plasma (p = 0.0523) and the consumption of ALA in the diet (p = 0.0039) were associated with high aerobic performance. Conclusions ALA in the diet of the athletes may be used as nutritional support to increase MFO and aerobic performance.